The detection of specific gene rearrangements in non-Hodgkin's lymphoma using the polymerase chain reaction. - Corbally, N. (Nature Publishing Group, 1992)
Characteristic gene rearrangements are present in most non-Hodgkin's lymphomas (NHL). These are usually detected by Southern blotting techniques. In this study, the ability of the polymerase chain reaction (PCR) to detect the t(14;18) chromosomal translocation and immunoglobulin heavy chain (IgH) gene rearrangement was evaluated. DNA from 14 follicular and 42 diffuse B-cell lymphomas was examined using oligonucleotide primers specific for opposing sides of the IgH gene rearrangement on chromosome 14 (towards conserved VH and JH sequences) and opposing sides of the t(14;18) chromosomal translocation (towards the major breakpoint region of the bcl-2 gene on chromosome 18 and conserved JH sequence on chromosome 14). The t(14;18) translocation was detected in 57% of follicular lymphomas and 21% of diffuse B-cell lymphomas. Clonal IgH gene rearrangements using PCR were detected in 50% follicular and 52% of the diffuse lymphomas. Either or both of these rearrangements were detected in 93% follicular and in 59% of diffuse lymphomas. PCR is a rapid and easy technique that can detect the abnormal rearrangement of the bcl-2 gene and clonal IgH rearrangement, indicating the presence of lymphoma. This may be of benefit in monitoring response to therapy and in predicting prognosis in this disease. IMAGES: